Effect of inflammation on voriconazole levels in patients with invasive pulmonary aspergillosis - Pinar Bakir Ekinci; Emre Kara; Ahmet G Er; Asli Pinar; Ahmet C Inkaya; Kutay Demirkan; Gokhan Metan; Omrum Uzun (Journal of Infection in Developing Countries)
Introduction: Voriconazole (VCZ) serum concentrations may be affected by many factors, such as drug-drug interactions, liver dysfunction, genetic polymorphism, and inflammation. This study aimed to determine the relationship between VCZ measured trough plasma levels and C-reactive protein levels in patients with coronavirus disease 2019 (COVID-19)-associated aspergillosis (CAPA) and invasive pulmonary aspergillosis (IPA).